Disproportionate Reduction of Serotonin Transporter May Predict the Response and Adherence to Antidepressants in Patients with Major Depressive Disorder: A Positron Emission Tomography Study with 4-[18F]-ADAM. (6th March 2015) - Yeh, Yi-Wei; Ho, Pei-Shen; Kuo, Shin-Chang; Chen, Chun-Yen; Liang, Chih-Sung; Yen, Che-Hung; Huang, Chang-Chih; Ma, Kuo-Hsing; Shiue, Chyng-Yann; Huang, Wen-Sheng; Shyu, Jia-Fwu; Wan, Fang-Jung; et al.
Abstract : Background: Many lines of evidence suggest the role of serotonin transporter (SERT)-mediated reuptake of serotonin in the pathophysiology and treatment of major depressive disorder (MDD). This study aimed to examine whether the pretreatment of SERT binding potential or SERT binding ratio between terminal projection regions relative to the midbrain raphe nuclei was associated with treatment outcomes to SERT-targeted antidepressants. Methods: We recruited 39 antidepressant-naïve patients with MDD and 39 heathy controls. Positron emission tomography with N, N -dimethyl-2-(2-amino-4-[ 18 F]fluorophenylthio)benzylamine (4-[ 18 F]-ADAM) was used to measure in vivo SERT availability prior to antidepressant treatment. The 21-item Hamilton Depression Rating Scale (HDRS) was use to assess the severity of depression from baseline to week 6. All the patients with MDD had HDRS scores of 18 or more. Results: Pretreatment SERT binding in the thalamus and striatum positively correlated with an early reduction in HDRS scores at week 3. Nonresponders and dropout patients showed a proportionate reduction in SERT binding in the terminal projection regions and midbrain compared to healthy controls. In contrast, a disproportionate reduction in SERT binding in the terminal projection regions relative to midbrain was observed in responders. Conclusions: The results of this study suggested that a disproportionate reduction in SERT binding between terminal projection regions and midbrain may predict better treatment outcomes in patients with MDD.